An additional list with new records of braconid wasps of the family braconidae (Hymenoptera) from Vietnam - Long, Khuat Dang; Achterberg, Cornelis van (Academia Journal of Biology, 2015)
Braconidae (Hymenoptera) is one of two most diverse families of Hymenoptera and both belong to the superfamily Ichneumonoidea, most braconid wasps are known as parasitoids of other insects damaging agricultural crops, many members of the parasitic braconid wasps are the important agents for biological control of insect pests. This paper presented the list of 210 braconid wasps of the family Braconidae from Vietnam with the information of the museums where the types are deposited, the published papers of the first record of braconid species in Vietnam, hosts and distribution of braconid species. Sixty two species recorded for the first time from Vietnam, which is 12.6% of the 492 braconid species belonging to 24 subfamilies now known from Vietnam. Additionally, there are 18 species listed with information about their hosts, being agricultural pests controlled to some degree by these parasitoids.